Using pollen in turbidites for vegetation reconstructions - Laura S. McDonald; Lorna J. Strachan; Katherine Holt; Adam D. McArthur; Philip M. Barnes; Katherine L. Maier; Alan R. Orpin; Mark Horrocks; Aratrika Ganguly; Jenni L. Hopkins; Helen C. Bostock (Journal of Quaternary Science, 2024)
Turbidites, deposited by sub‐aqueous gravity flows, are common in sedimentary archives worldwide and present a unique challenge and opportunity when reconstructing past vegetation through pollen analysis. When sampling pollen from a sediment core for palaeovegetation records, it is common practice to target background sediments (i.e. pelagic sediment) and avoid sampling turbidites, as they are presumed to portray a misleading picture of past vegetation. This assumption stems from our limited understanding of pollen abundance and distribution through turbidites, meaning that palynologists overlook deposits that could potentially be used to reconstruct past vegetation and climate. We present pollen assemblage and sedimentological data from four recent (